Effect of the secretome of multipotent mesenchymal stromal cells induced by dexamethasone in vitro on the expression of phospho-NF-κB p65 and Ki-67 in mononuclear cells - Polina A. Golubinskaya; Maksim V. Puzanov; Svetlana Y. Burda; Darya A. Kostina; Yuriy E. Burda (Belgorod National Research University, 2021)
Introduction: To investigate the influence of secretomes from native and dexamethasone-treated adipose-derived multipotent mesenchymal stromal cells (MMSC) on the proliferation of mononuclear cells (MNCs) and on their expression of phospho-NF-κB p65 in vitro. Materials and Methods: MMSCs were isolated from the fat of 5 healthy donors. The cells were grown in culture up to passage four, then treated with dexamethasone for 3 hours, washed off the preparations, and incubated in a serum-free medium for 48 hours. Some of the cells were not treated with dexamethasone. Supernatants from cell cultures were concentrated by ultrafiltration, standardized by the content of galectin-1, sterilized, and added to MNCs from peripheral blood of 8 healthy donors. MNCs were isolated in a Ficoll density gradient according to a standard protocol. The expression of phospho-NF-κB p65 and Ki-67 in MNCs under the influence of MMSC secretomes in isotypic and negative controls was determined on a flow cytometer. Results and Discussion: The expression of phospho-NF-kκB p65 and Ki-67 is decreased by the MMSC secretome. At the same time, a statistically significant decrease in phospho-NF-κB p65 by 36.2% (p < 0.05) is observed when using a secretome from native cells. Ki-67 expression is reduced by 42.3% (p < 0.05) under the influence of a secretome from dexamethasone-treated MMSCs. Conclusion: The MMSC secretome, as well as MMSCs themselves, has an anti-inflammatory effect due to the effect on the expression of the active form of NF-κB and the proliferative activity of mononuclear cells. At the same time, pretreatment of cells with dexamethasone reduces the effect on phospho-NF-κB expression and increases the inhibitory effect on MNC proliferation.